How Does Suppliers' Fairness Affect the Relationship Quality of Agricultural Product Supply Chains?. (19th February 2018) - Sun, Yuling; Liu, Zehua; Yang, Hui
Abstract : Although many studies have suggested that the relationship between different supply chain members significantly affects agricultural product quality, suppliers' perceptions of fairness, which greatly influence their decisions on building the relationship quality, are often overlooked. Particularly, the empirical evidence to investigate the impacts of suppliers' fairness on the relationship quality and the factors that affect the suppliers' fairness is missing, and therefore this knowledge gap needs to be filled by new research. Herein, we conducted a survey of 450 agricultural product suppliers and systemically analyzed the impact of antecedents on fairness perception and the impact of fairness perception on relationship quality. In addition, we developed a structural equation model and found that information sharing and price satisfaction had significantly positive effects on procedural fairness and distributive fairness, respectively. Furthermore, our studies demonstrated that procedural fairness is more important in improving the relationship quality than distributive fairness. However, supplier dependence is another important impact factor, and it greatly decreases the positive effects of suppliers' fairness on relationship quality. In summary, the study results provide several managerial implications and extend our understanding of the importance of suppliers' fairness in the relationship quality, which involves product development with respect to the supplier's performance.